The Influence of Government Accounting Standards and Financial Report Quality on Government Performance Accountability in Kecamatan Secanggang - Silvi Dwi Utari; Oktarini Khamilah Siregar; Agus Tripriyono (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
The purpose of this study is to determine the effect of Government Accounting Standards and the quality of financial reports on the accountability of the performance of the Secanggang District Village government. The population in this study was taken from the Secanggang District Village apparatus. The sampling technique in this study used purposive sampling with a total of 51 respondents. The analysis method used in this study discusses the independent variables against the dependent variable. The variables in this study are government accounting standards, and the quality of financial reports as the independent variable and government performance accountability as the dependent variable. The results of the study after being analyzed using SmartPLS 4 show that government accounting standards have a significant effect on government performance accountability, this is indicated by the original sample value of 0.432 (positive), the construct T-Statistic value is 4.808 (> 1.96) and the p-value is 0.000 (<0.05). The quality of financial reports has a significant effect on government performance accountability, this is indicated by the original sample value of 0.532 (positive), the construct T-Statistic value is 5.969 (> 1.96) and the p-value is 0.000 (<0.05). Government accounting standards and the quality of financial reports have a simultaneous effect on performance accountability, as indicated by the calculated F value of 82.321 and the p-value is much smaller than 0.05, namely 0.000 <0.05.